The ms. Clm 14011 of Bayerische Staatsbibliothek, München: Stylistic Coexistences and Illustrative Aspects in a Late XIII Century Genoese Legal Manuscript - Volpera, Federica (Eikón / Imago, 2023)
This article presents the results of a close investigation on the manuscript Clm 14011 preserved in the Bayerische Staatsbibliothek of München. The manuscript was produced in Genoa at end of the XIII century and contains the Decretals of Gregory IX, the Collectio III of Innocent IV and the Constitutiones of Gregory X. The style of miniature and multicolored initials suggests the work of two different artists: the first, who painted the miniature at the beginning of each book, was deeply influenced by Paduan school; the second, who painted the initials, was a Genoese artist who followed the language of the so-called Master of ms. Lat. 42. Finally, the analysis of the iconography of each miniatures reveals how religious themes and details were reused in the illustrations of a legal manuscript.